The ages of globalization : geography, technology, and institutions - Sachs, Jeffrey (New York : Columbia University Press, 2020)
"Today's most urgent problems are fundamentally global. They require nothing less than concerted, planetwide action if we are to secure a long-term future. But humanity's story has always been on a global scale, and this history deeply informs the present. In this book, Jeffrey D. Sachs, renowned economist and expert on sustainable development, turns to world history to shed light on how we can meet the challenges and opportunities of the twenty-first century. Sachs takes readers through a series of six distinct waves of technological and ideological change, starting with the very beginnings of our species and ending with reflections on present-day globalization. Along the way, he considers how the interplay of geography, technology, and institutions influenced the Neolithic revolution; the spread of land-based empires; the opening of sea routes from Europe to Asia and the Americas; and the industrial age. The dynamics of these past waves, Sachs contends, give us new perspective on the ongoing processes taking place in our own time-and how we should work to guide the change we need. In light of this new understanding of globalization, Sachs emphasizes the need for new methods of international governance and cooperation to achieve economic, social, and environmental objectives aligned with sustainable development. The Ages of Globalization is a vital book for all readers aiming to make sense of our rapidly changing world"--
Includes bibliographical references and index.
Keywords: Globalization -- History